2020
DOI: 10.1103/physrevlett.124.203401
|View full text |Cite
|
Sign up to set email alerts
|

Mode-Specific Vibrational Autodetachment Following Excitation of Electronic Resonances by Electrons and Photons

Abstract: Electronic resonances commonly decay via internal conversion to vibrationally hot anions and subsequent statistical electron emission. We observed vibrational structure in such an emission from the nitrobenzene anion, in both the 2D electron energy loss and 2D photoelectron spectroscopy of the neutral and anion, respectively. The emission peaks could be correlated with calculated nonadiabatic coupling elements for vibrational modes to the electronic continuum from a nonvalence dipole-bound state. This autodeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…The dipole-bound state autodetaches through modespecific vibrational autodetachment invoked by modes that strongly couple the dipole-moment to the continuum. 31,33,36,37 These modes would be similar to the modes of the final neutral ground state. The lowest frequency mode of a 0 symmetry for the D 0 electronic state was calculated at n 33 = 310 cm À1 and is moderately infra-red active.…”
Section: Autodetachment Dynamics Leading To the Low-eke Vibrational Structurementioning
confidence: 94%
See 2 more Smart Citations
“…The dipole-bound state autodetaches through modespecific vibrational autodetachment invoked by modes that strongly couple the dipole-moment to the continuum. 31,33,36,37 These modes would be similar to the modes of the final neutral ground state. The lowest frequency mode of a 0 symmetry for the D 0 electronic state was calculated at n 33 = 310 cm À1 and is moderately infra-red active.…”
Section: Autodetachment Dynamics Leading To the Low-eke Vibrational Structurementioning
confidence: 94%
“…This vibrational mode satisfies the criterion for efficient electron ejection or 'shake off' when directly exciting the dipole-bound state -modulation of the dipole-bound state orbital by the vibrational motion -and would generate a similar (s-wave) low-eKE spectrum to mode-specific autodetachment proposed in mechanism (b). 33,[36][37][38][39][40][41] This detachment mechanism usually involves Dv = À1, where v is a vibrational level, although anharmonicity associated with low-frequency bending modes has shown that Dv = À2 also occurs in this system. 23 The proposed low frequency mode, n 33 , is likely to be populated at T E 300 K according to Boltzmann statistics.…”
Section: Autodetachment Dynamics Leading To the Low-eke Vibrational Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Interconnections between valence states of anions and dipole-bound states have also been identified in the opposite direction (bifurcation of the excited state wavepacket leading to the formation of a non-valence state) for a common anionic chromophore, 55 and the stability of such orbitals in the presence of perturbing molecules has also been studied by the same group. 56 Very recently, Anstöter et al 57 showed that the observed emission peaks from the vibrational structure of the nitrobenzene anion can be correlated with an autodetachment mechanism via dipole-bound state formation. In all these cases, dipole-bound states are formed at very low energy, below the lower energy limit of the present experimental study (0.4 eV).…”
Section: And References Therein)mentioning
confidence: 99%
“…The latter relaxation channel, dissociative electron attachment (DEA), is ubiquitous in molecules of various types, even though its underlying working mechanisms are far from understood. 19 Transient anions can also be populated by photoexcitation of an electronically bound anion, 20,21 possibly accessing different regions of the PESs and leading to distinct decaying channels. Related processes include dissociative recombination 22 and associative detachment, the latter being the inverse process of DEA.…”
Section: Introductionmentioning
confidence: 99%